Hernial SAC Ligation in Hernioplasty of Indirect Hernia - A Needless Step - MUHAMMAD USMAN ASLAM, AHSEN NAZIR, BALAKH SHER ZAMAN, MUHAMMAD FAHEEM ANWER (Journal of Fatima Jinnah Medical University, 2018)
Objectives. To evaluate the effect of high sac ligation in Lichtenstein Indirect inguinal hernia repair on post operative pain. Methodology: This study consisting of 100 patients of clinically diagnosed right or left indirect inguinal hernia with age ranging from 16-80 yrs, was conducted in the department of surgical unit II, Jinnah Hospital, Lahore. Patients were divided randomly in two equal groups. Group A included patients undergoing high sac ligation while group B included patients of sac reduction. The main outcome measure was mean postoperative pain score using visual analog scale on 1st, 7th and 10th post operative days. Results: 78% of the patients were between 20 to 50 yrs of age with male to female ratio 99:1. 60% of the patients had presented with right inguinal hernia and 40% with left inguinal hernia. Postoperatively mean pain scores in patients who underwent sac reduction were 3.30 + 0.70 on 1st post op day, 2.22 + 0.58 on 7th and 0.32 + 0.47 on 10th post op day, while mean pain scores in patients who underwent high sac ligation were 4.34 + 0.82 on 1st post op day, 3.34 + 0.64 on 7th and 2.40 + 0.53 on 10th post op day. Conclusion: Ligation of the hernial sac in inguinal hernia surgery is not only unnecessary and time consuming but also leads to increased post-operative pain.